2005
DOI: 10.1093/qjmed/hci134
|View full text |Cite
|
Sign up to set email alerts
|

Impaired glucose metabolism in patients with acute stroke and no previous diagnosis of diabetes mellitus

Abstract: Impaired glucose tolerance and previously unrecognized diabetes could be detected early in the stroke course, and persisted after 3 months in more than two-thirds of our patients. Post-load hyperglycaemia during the acute phase of stroke may be useful in identifying patients with abnormal glucose metabolism, which places them at risk for adverse outcomes, including cardiovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
80
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(92 citation statements)
references
References 38 publications
9
80
0
3
Order By: Relevance
“…[18][19][20][21] We infer that the most important reason was a high prevalence and low awareness of DM in China. A recent national-wide study showed that the prevalence of DM among Chinese aged 60 to 69 years was 25%, 22 and the proportion of those knowing of their DM was only 40%.…”
Section: August 2016mentioning
confidence: 89%
See 1 more Smart Citation
“…[18][19][20][21] We infer that the most important reason was a high prevalence and low awareness of DM in China. A recent national-wide study showed that the prevalence of DM among Chinese aged 60 to 69 years was 25%, 22 and the proportion of those knowing of their DM was only 40%.…”
Section: August 2016mentioning
confidence: 89%
“…[18][19][20][21] A European study had investigated the prevalence of NDDM using the newly proposed HbA1c criteria and indicated that the prevalence of NDDM was 25% in patients with stroke or transient ischemic attack. 20 In our study, 32% of the patients were diagnosed using the glucose-based criteria, ‡P value between DN (total) and non-DM.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies from Europe and Japan in which OGTT was performed supplied either no diagnosis of IFG or small sample sizes. 13,24 Data on the prevalence of IFG and IGT among patients with intracerebral hemorrhage or SAH remained scarce. Our results indicate high prevalence of IGT and newly diagnosed DM in patients with intracerebral hemorrhage and SAH, which suggested that the identification of abnormal glucose regulation should be emphasized in the patients not only with ischemic stroke but also with intracerebral hemorrhage and SAH, and OGTT should be performed in all the stroke patients without history of diabetes after acute stage of stroke.…”
Section: Jia Et Al Abnormal Glucose After Stroke 653mentioning
confidence: 99%
“…The reported prevalence of diabetes at discharge in a cohort of 106 people (median age 71 years) with acute ischaemic stroke and no history of diabetes was 46% based on an OGTT (Vancheri et al, 2005). At admission a further 29% already had a diagnosis of diabetes.…”
Section: Case Detection and Diagnosis June 2009mentioning
confidence: 99%